Electrolyte and lithium ion battery
By adding silicon oxy compounds and carbodiimide compounds containing unsaturated bonds to the electrolyte of lithium-ion batteries, the problem of poor battery circulation performance caused by the expansion of silicon negative electrode is solved, and the battery performance and safety are improved.
Patent Information
- Application Number
- CN202411981078.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The volume expansion of the silicon negative electrode embedded/deliquefied volume in lithium-ion batteries leads to poor battery circulation performance, and the thickening of SEI film consumes active lithium.
The silicon oxy compound (first additive) and carbodiimide compound (second additive) containing unsaturated bonds are added to the electrolyte to inhibit the negative impact of the expansion of the silicon negative electrode. The first additive forms a new Si-O-Si bond by reacting with the silicon hydroxyl group and is fixed on the surface of the silicon negative electrode, while the second additive absorbs water and acid in the electrolyte to reduce the impact on the first additive.
Effectively suppress the negative impact of silicon negative electrode expansion, improve the circulation performance and initial impedance of lithium-ion batteries, and improve the overall performance and safety of the battery.
Smart Images

Figure BDA0005221950150000011 
Figure BDA0005221950150000041 
Figure FDA0005221949980000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power batteries, and in particular to an electrolyte and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries are widely used in electric vehicles due to their high energy density and long cycle life. With the development of the electric vehicle industry, the driving range has become an important reason limiting the further development of lithium-ion batteries. Silicon anodes are widely considered to be the best choice for the anodes of next-generation products due to their high theoretical capacity. However, the silicon anode has a large volume expansion due to lithium insertion / extraction, which leads to poor battery cycle performance. At the same time, when conventional electrolyte faces the silicon anode, the SEI film formed will continue to thicken during the continuous expansion and contraction of the silicon anode, and the active lithium will be continuously consumed, resulting in poor cycle performance of lithium-ion batteries.
[0003] Therefore, developing new electrolytes suitable for use with silicon negative electrode systems, improving the cycle performance of lithium-ion batteries, and improving the overall performance of batteries will help break through the limitations of existing technologies, thereby promoting the development of silicon negative electrode system batteries and enhancing the commercial application prospects of silicon negative electrodes. Summary of the invention
[0004] In view of the shortcomings of the prior art mentioned above, the purpose of the present invention is to provide an electrolyte and a lithium-ion battery, by adding new additives to the electrolyte and then applying them to lithium-ion batteries to improve the battery cycle performance, etc., enhance the overall performance of the battery, and solve the negative impact caused by the current expansion of silicon negative electrodes, thereby improving the prospects for large-scale commercial promotion of silicon negative electrodes.
[0005] To achieve the above-mentioned object and other related objects, the present invention provides an electrolyte, comprising an electrolyte, a solvent and an additive, wherein the additive comprises at least a first additive and a second additive, and the first additive is selected from a silicon-oxygen compound containing an unsaturated bond having a chemical general formula as shown in formula (I):
[0006]
[0007] In formula (I), R1, R2, R3, R4 and R5 are each selected from at least one of tert-butyl, 1,1-dimethoxyethyl ether and 1,1-diethylpropyl;
[0008] The second additive is selected from carbodiimide compounds having a general chemical formula as shown in formula (II):
[0009] R6-N=C=N-R7
[0010] (II)
[0011] In formula (II), R6 and R7 are each selected from at least one of a substituted or unsubstituted alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 12 carbon atoms, or a substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms; if substituted, the substituent is a halogen or an alkyl group having 1 to 12 carbon atoms.
[0012] Furthermore, based on the total mass of the electrolyte, the mass percentage of the first additive is 0.1% to 3%.
[0013] Furthermore, based on the total mass of the electrolyte, the mass percentage of the second additive is 0.01% to 1%.
[0014] Furthermore, the electrolyte is a lithium salt, and the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonylimide, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, lithium difluorooxalatoborate, lithium difluorophosphate or lithium trifluoromethylsulfonate.
[0015] Furthermore, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the mass percentage of lithium hexafluorophosphate in the electrolyte is greater than the mass percentage of lithium bis(fluorosulfonyl)imide in the electrolyte.
[0016] Furthermore, based on the total mass of the electrolyte, the mass percentage of the lithium hexafluorophosphate is 11% to 15%, and the mass percentage of the lithium bis(fluorosulfonyl)imide is 1% to 3%.
[0017] Furthermore, the solvent is selected from at least one of carbonate solvents, carboxylate solvents, ether solvents or nitrile solvents.
[0018] The present invention also provides a lithium ion battery, comprising the electrolyte as described above in the claims.
[0019] Further, the lithium-ion battery comprises a negative electrode plate, the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer coated on at least one side surface of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material;
[0020] The negative electrode active material is selected from at least one of silicon, silicon oxide compounds or silicon carbon compounds; or, the negative electrode active material includes a first negative electrode active component and a second negative electrode active component, the first negative electrode active component is selected from at least one of silicon, silicon oxide compounds or silicon carbon compounds, and the second negative electrode active component is selected from at least one of graphite, soft carbon, hard carbon, artificial graphite or natural graphite.
[0021] Further, the lithium-ion battery comprises a positive electrode plate, the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material;
[0022] The positive electrode active material is selected from at least one of lithium nickel manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide.
[0023] As described above, the electrolyte and lithium ion battery of the present invention have the following beneficial effects:
[0024] 1. The present invention adds two additives to the electrolyte, namely, the first additive, a silicon-oxy compound containing an unsaturated bond shown in formula (I), and the second additive, a carbodiimide compound shown in formula (II). The combination of the two can effectively inhibit the negative impact caused by the expansion of the silicon negative electrode. Among them, the -Si-O-Si- group in the first additive can react with the residual silanol group on the surface of the silicon negative electrode to form a new Si-O-Si bond, so that the first additive is fixed on the surface of the silicon negative electrode; the R group in the first additive is a group with a large steric hindrance (such as tert-butyl, 1,1-dimethoxyethyl ether, 1,1-diethylpropyl), and its main function is that when the silicon negative electrode expands, the group can diffuse due to steric hindrance, greatly reducing the fresh exposed surface caused by the volume expansion of the silicon negative electrode; the first additive also contains an unsaturated bond, which can polymerize adjacent first additives and reduce the failure of the first additive caused by the breakage of Si-O-Si bonds; in addition, the Si-O-Si bond formed by the reaction of the first additive with the silanol group is easily attacked by hydrofluoric acid (HF) in the electrolyte, resulting in the breakage of the Si-O bond, which reduces the effect of reducing the first additive, so it is used in combination with the second additive. The main function of the second additive is to absorb water and acid in the electrolyte and reduce the influence of HF formed in the electrolyte on the first additive.
[0025] 2. The present invention also limits the amount of additives in the electrolyte. Only by reasonably regulating the amount of the first additive and the second additive within a specific range can the negative impact caused by the expansion of the silicon negative electrode be effectively suppressed, and the best balance point can be found between effectively improving the battery cycle performance and initial impedance and ensuring the battery performance, thereby effectively improving the overall performance and safety of the battery.
[0026] In summary, applying the electrolyte provided by the present invention to lithium-ion batteries constructed based on a silicon negative electrode system can effectively solve the negative impact caused by the expansion of the silicon negative electrode, thereby effectively improving the overall performance of the battery and improving the battery safety performance, thereby improving the prospects for large-scale commercialization of silicon negative electrodes. DETAILED DESCRIPTION
[0027] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0028] In the present invention, unless otherwise specified, the term "plurality" means two or more.
[0029] The character " / " indicates that the objects before and after are in an "or" relationship. For example, A / B means: A or B.
[0030] The term "and / or" is a description of the association relationship between objects, indicating that three relationships can exist. For example, A and / or B means: A or B, or, A and B.
[0031] An embodiment of the present invention provides an electrolyte, comprising an electrolyte, a solvent and an additive, wherein the additive comprises at least a first additive and a second additive, and the first additive is selected from a silicon-oxygen compound containing an unsaturated bond having a chemical formula as shown in formula (I):
[0032]
[0033] In formula (I), R1, R2, R3, R4 and R5 are each selected from at least one of tert-butyl, 1,1-dimethoxyethyl ether and 1,1-diethylpropyl;
[0034] The second additive is selected from carbodiimide compounds having a general chemical formula as shown in formula (II):
[0035] R6-N=C=N-R7 (II),
[0037] In formula (II), R6 and R7 are each selected from at least one of a substituted or unsubstituted alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted alkenyl group having 2N12 carbon atoms, or a substituted or unsubstituted cycloalkyl group having 3N12 carbon atoms; if substituted, the substituent is a halogen or an alkyl group having 1 to 12 carbon atoms.
[0038] In lithium-ion batteries, the electrolyte plays the role of conducting ions, providing ion channels, and maintaining chemical stability. The various components in the electrolyte can be divided into electrolyte lithium salts, solvents, and additives according to their functions and dosages. Lithium salts are mainly used to provide lithium ions to form ion channels. In the entire electrochemical system of the battery, the directional movement of lithium ions and electrons generates electricity. Lithium salts have a great influence on the energy density, power density, wide electrochemical window, cycle life, and safety performance of lithium batteries; solvents are used to dissolve lithium salts and additives; additives are substances added in small amounts to the electrolyte. There are many types and each plays a different role. For example, they can have different improvement effects on the high and low temperature performance, cycle performance, and film-forming performance of the battery.
[0039] In the above embodiment of the present invention, two additives are added to the electrolyte, namely, a first additive, a silicon-oxy compound containing an unsaturated bond shown in formula (I), and a second additive, a carbodiimide compound shown in formula (II). The combination of the two can effectively inhibit the negative impact of the expansion of the silicon negative electrode. Among them, the -Si-O-Si- group in the first additive can react with the residual silanol group on the surface of the silicon negative electrode to form a new Si-O-Si bond, so that the first additive is fixed on the surface of the silicon negative electrode; the R group in the first additive is a group with a large steric hindrance (such as tert-butyl, 1,1-dimethoxyethyl ether, 1,1-diethylpropyl), and its main function is that when the silicon negative electrode expands, the group can diffuse due to steric hindrance, greatly reducing the fresh exposed surface caused by the volume expansion of the silicon negative electrode; the first additive also contains an unsaturated bond, which can polymerize adjacent first additives and reduce the failure of the first additive caused by the breakage of Si-O-Si bonds; in addition, the Si-O-Si bond formed by the reaction of the first additive with the silanol group is easily attacked by hydrofluoric acid (HF) in the electrolyte, resulting in the breakage of the Si-O bond, which reduces the effect of reducing the first additive, so it is used in combination with the second additive. The main function of the second additive is to absorb water and acid in the electrolyte and reduce the influence of HF formed in the electrolyte on the first additive.
[0040] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the first additive is 0.1% to 3%, preferably 0.1% to 1%. If the amount of the first additive is too much, that is, exceeds the limit of 3%, it will affect the impedance and cycle performance of the battery. On the contrary, if the amount of the first additive is too little, that is, below the critical value of 0.1%, it will not be able to effectively improve the battery cycle performance and reduce the battery impedance.
[0041] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the second additive is 0.01% to 1%, preferably 0.1% to 0.3%. If the amount of the second additive is too much, that is, exceeds the limit of 1%, the battery performance cannot be further improved. On the contrary, if the amount of the second additive is too little, that is, below the critical value of 0.01%, it is impossible to effectively improve the battery cycle performance and reduce the battery impedance.
[0042] Therefore, the dosage of the first additive and the second additive is reasonably adjusted within the range defined in the above embodiment to effectively suppress the negative impact caused by the expansion of the silicon negative electrode, and find the best balance between effectively improving the battery cycle performance and initial impedance and ensuring the battery performance, thereby effectively improving the overall performance and safety of the battery.
[0043] In some embodiments, the electrolyte is a lithium salt, and the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonylimide, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, lithium difluorooxalatoborate, lithium difluorophosphate, or lithium trifluoromethylsulfonate.
[0044] In some embodiments, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the mass percentage of lithium hexafluorophosphate in the electrolyte is greater than the mass percentage of lithium bis(fluorosulfonyl)imide in the electrolyte.
[0045] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the lithium hexafluorophosphate is 11% to 15%, and the mass percentage of the lithium bis(fluorosulfonyl)imide is 1% to 3%.
[0046] In some embodiments, the solvent is selected from at least one of carbonate solvents, carboxylate solvents, ether solvents or nitrile solvents. Among them, carbonate solvents are selected from ethylene carbonate, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, polycarbonate, etc., carboxylate solvents are selected from ethyl formate, ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, etc., ether solvents are selected from ethylene glycol dimethyl ether, diethanol diethyl ether, etc., and nitrile solvents are selected from acetonitrile, propionitrile, butyronitrile, valeronitrile, etc. The present invention does not limit the type of solvent, and a single solvent or a mixed solvent can be used.
[0047] Another embodiment of the present invention provides a lithium-ion battery, comprising the electrolyte as claimed in the claims, and also comprising a shell and a bare cell disposed in the shell, wherein the bare cell comprises a positive electrode sheet, a separator and a negative electrode sheet.
[0048] In a specific embodiment, the preparation method of the lithium-ion battery includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence to ensure that a separator is provided between any positive electrode sheet and any negative electrode sheet, and obtaining a multilayer laminate body by winding, and loading it into a battery casing as a bare cell. Finally, injecting an electrolyte into the casing once or multiple times so that the bare cell is completely immersed in the electrolyte. In other words, the electrolyte is injected into and fills the entire internal space of the battery, and the positive electrode sheet, the separator, and the negative electrode sheet are completely immersed in the electrolyte.
[0049] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material; the negative electrode active material is selected from at least one of silicon, silicon oxide compounds or silicon carbon compounds; or, the negative electrode active material includes a first negative electrode active component and a second negative electrode active component, wherein the first negative electrode active component is selected from silicon, silicon oxide compounds (SiO x , 0<x<2) or at least one of silicon-carbon compounds, the second negative electrode active component is selected from at least one of graphite, soft carbon, hard carbon, artificial graphite or natural graphite, and the mass ratio of the first negative electrode active component to the second negative electrode active component can be, for example, 2-20:8-98. In addition, the negative electrode current collector is, for example, selected from any one of a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector or a stainless steel current collector, and the thickness of the negative electrode current collector is, for example, 8μm to 15μm. In a specific embodiment, the negative electrode current collector is, for example, copper foil, and the thickness of the copper foil is, for example, 13μm.
[0050] In some embodiments, the negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder and a thickener, etc. The mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener can be, for example, (90-96): (1-2): (1-3): (2-5). Among them, the conductive agent is, for example, selected from any one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes or graphene. The binder is, for example, selected from any one or more of carboxymethyl cellulose sodium (CMC-Na), polyvinylidene fluoride, polyethylene oxide, polyamide, polypropylene, polyacrylate, polyethylene ether, polymethyl methacrylate, polyhexafluoropropylene or styrene-butadiene rubber. The thickener is, for example, CMC-Na.
[0051] In a specific embodiment, the negative electrode active material is selected from silicon dioxide (SiO), the conductive agent is selected from acetylene black, and the binder is selected from sodium carboxymethyl cellulose. The negative electrode active material, the conductive agent, and the binder are mixed, for example, in a mass ratio of 96:2:2, deionized water is added, and mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained through cold pressing and slitting. In other embodiments, the negative electrode sheet can also be obtained by any other method of forming a negative electrode sheet.
[0052] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material; the positive electrode active material is selected from at least one of lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, preferably at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide. Further, in some embodiments, the positive electrode active material is selected from a ternary positive electrode material, such as a ternary positive electrode material having a chemical formula of Li x Ni y Co z Mn t M γ O 2-δ A ternary positive electrode material, wherein M is selected from at least one of Cr, Zr, Ca, Mg, Cu, Ti, Al, Mo, W or Zn, 0.9<x<1.1, 0.65≤y<1.0, 0≤z<0.5, 0≤t<0.5, y+z+t+γ=1, 0≤δ≤0.1, to improve the energy density and cycle life of the lithium-ion battery. In addition, the positive electrode collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Among them, the thickness of the positive electrode collector is, for example, 8μm to 15μm. Further, in a specific embodiment, the positive electrode collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm.
[0053] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a binder and a conductive agent, and the like, and the mass ratio of the positive electrode active material, the conductive agent and the binder can be, for example, (90-98): (1-5): (1-5). The binder is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR). The conductive agent is, for example, selected from any one or more of conductive carbon black (SuperP), acetylene black, carbon nanotubes or graphene.
[0054] In one specific embodiment, the positive electrode active material is, for example, LiNi 0.8 Mn 0.1 Co 0.1 02, the binder is selected from polyvinylidene fluoride, and the conductive agent is selected from acetylene black. After mixing the positive electrode active material, the conductive agent and the binder, for example, in a mass ratio of 95:3:2, an organic solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. Among them, the organic solvent is selected from N-methylpyrrolidone (NMP), for example. The positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode sheet is obtained through cold pressing and slitting. In other embodiments, the positive electrode sheet can also be obtained by any other method of forming a positive electrode sheet.
[0055] In some embodiments, the separator is, for example, a polyethylene (PE) film, a polypropylene (PP) film, a glass fiber film, or a composite film, and the thickness of the separator is, for example, 9 μm to 15 μm.
[0056] In some embodiments, the diaphragm includes a base film and a coating coated on the base film, wherein the base film is, for example, a PE film, a PP film, a glass fiber film or a composite film, and the thickness of the diaphragm is, for example, 8 μm to 10 μm; the coating is, for example, a nano-aluminum oxide coating, and the coating thickness is, for example, 2 μm to 4 μm.
[0057] The following specific examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range according to the description herein, and are not limited to the specific values exemplified below.
[0058] According to the dosage of the first additive and the second additive in the electrolyte of Example 1N12 and Comparative Examples 1 to 3 shown in Table 1, the electrolyte, positive electrode sheet, negative electrode sheet and separator were prepared according to the following method, and then lithium-ion batteries were made and performance tests were carried out. The test results are shown in Table 1.
[0059] 1. Preparation of electrolyte:
[0060] In an argon glove box with a moisture content of less than 0.1 ppm and an oxygen content of less than 0.1 ppm, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate are mixed uniformly in a mass ratio of 3:5:2 to obtain a mixed solvent, and then dried lithium hexafluorophosphate and lithium bisfluorosulfonyl imide, as well as a first additive and / or a second additive are added to the mixed solvent, and the electrolyte is obtained after mixing uniformly. In the obtained electrolyte, based on the total mass percentage of the electrolyte being 100%, the mass percentage of lithium hexafluorophosphate is 13%, the mass percentage of lithium bisfluorosulfonyl imide is 2%, and the mass percentage of the mixed solvent is adjusted according to the amount (i.e., mass percentage) of the first additive and the second additive.
[0061] Among them, R1, R2, R3, R4 and R5 of the first additive used in Examples 1 to 9 and Example 12 are all tert-butyl (), R1, R2, R3, R4 and R5 of the first additive used in Example 10 are all 1,1-dimethoxyethyl ether, and R1, R2, R3, R4 and R5 of the first additive used in Example 11 are all 1,1-diethylpropyl.
[0062] R6 and R7 of the second additive used in Examples 1N11 are both methyl groups, and R6 and R7 of the second additive used in Example 12 are both fluoromethyl groups.
[0063] 2. Preparation of positive electrode sheet:
[0064] The positive electrode active material LiNi 0.8 Mn 0.1 Co 0.1O2, conductive agent acetylene black, and binder polyvinylidene fluoride were mixed in a mass ratio of 95:3:2, and N-methylpyrrolidone was added. The mixture was stirred in a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil with a thickness of 13 μm, and then dried at room temperature and transferred to an oven for drying. After cold pressing and slitting, a positive electrode sheet was obtained.
[0065] 3. Preparation of negative electrode sheet:
[0066] The negative electrode active material silicon dioxide, the conductive agent acetylene black, and the binder sodium carboxymethyl cellulose are mixed in a mass ratio of 96:2:2, deionized water is added, and mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry is coated on a copper foil with a thickness of 13μm, and then transferred to an oven for drying after drying at room temperature. After cold pressing and slitting, the negative electrode sheet is obtained. 4. Preparation of the diaphragm:
[0067] A polyethylene film with a thickness of 8 μm was selected as a base film, and a nano-aluminum oxide coating with a thickness of 3 μm was coated on the base film to obtain a separator.
[0068] 5. Preparation of batteries:
[0069] The positive electrode sheet, the separator, and the negative electrode sheet are wound in sequence, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and a cylindrical bare battery cell is obtained. Then, it is placed in a round shell, dried in a vacuum oven, and the prepared electrolyte is injected and sealed, and the electrolyte is formed to obtain a lithium-ion battery.
[0070] 6. Performance test method:
[0071] 6.1、Cyclic test:
[0072] At 25°C, charge the lithium-ion battery at a constant current of 1 / 3C to 4.25V, then charge at a constant voltage to a current of 0.05C. Then discharge the battery at a constant current of 1 / 3C to 2.5V. Record the capacity C0, repeat the above charge and discharge steps 1000 times, record the discharge capacity C1 of 1000 cycles, and calculate the battery's cycle capacity retention rate according to the following formula:
[0073] Cycle capacity retention rate = C1 / C0*100%.
[0074] 6.2. Direct Current Resistance (DCR) growth rate test:
[0075] At 25°C, charge the uncycled lithium-ion battery at 1 / 3C constant current to 4.25V, then charge at constant voltage to a current of 0.05C. Then discharge the battery at 1 / 3C constant current to 2.5V. Repeat the above charging steps and record the charging capacity as C1. Discharge the battery at 1 / 3C constant current to (50%*C1), record the initial voltage as V2. Discharge the battery at 1C constant current for 30s, record the terminal voltage as V3. Calculate DCR1 according to the following formula:
[0076] DCR1 = (V2 - V3) / (C1*1).
[0077] Use the same method to test the cycled cells, record them as DCR2, and calculate the DCR growth rate according to the following formula:
[0078] DCR growth rate = DCR2 / DCR1*100%.
[0079] Table 1
[0080] Amount of the first additive / % Amount of the second additive / % Cycle capacity retention rate / % DCR growth rate / % Example 1 0.1 0.1 79.4% 39.9% Example 2 0.5 0.1 83.4% 31.5% Example 3 1 0.1 83.3% 32.6% Example 4 0.5 0.2 88.6% 21.7% Example 5 0.5 0.3 88.2% 22.4% Example 6 3 0.1 83.2% 33.1% Example 7 0.5 0.01 75.6% 60.8% Example 8 0.5 1 88.4% 23.4% Example 9 0.01 0.1 74.2% 58.2% Example 10 0.5 0.2 87.6% 23.7% Embodiment 11 0.5 0.2 87.3% 24.1% Example 12 0.5 0.2 88.7% 23.7% Comparative Example 1 0.5 0 75.7% 60.3% Comparative Example 2 0 0.2 74.3% 59.2% Comparative Example 3 0 0 73.1% 64.0%
[0081] From the data in Table 1, we can draw the following conclusions:
[0082] By comparing Examples 4, 10 to 12 with Comparative Example 1N3, it can be seen that the combination of the first additive and the second additive can effectively improve the battery cycle performance and reduce the battery impedance.
[0083] By comparing Examples 1 to 3, 6, and 9 with Comparative Example 2, it can be seen that as the amount of the first additive increases from 0.1% to 3%, the battery cycle capacity retention rate shows a trend of first increasing and then decreasing, while the DCR growth rate shows a trend of first decreasing and then increasing, but both can effectively improve the battery cycle performance and reduce the battery impedance; but if the amount is too small or the first additive is not added to the electrolyte, the battery cycle performance cannot be effectively improved and the battery impedance cannot be reduced; and if the amount is too large, the impedance and cycle performance of the battery will be affected. Therefore, the amount of the first additive is suitable to be controlled within the range of 0.1% to 3%, and the optimal amount is 0.1 to 1%.
[0084] Comparing Examples 2, 4, 5, 7, and 8 with Comparative Example 1, it can be seen that as the amount of the second additive increases from 0.1% to 1%, the battery cycle capacity retention rate shows a trend of first increasing and then decreasing, while the DCR growth rate shows a trend of first decreasing and then increasing, but they can all effectively improve the battery cycle performance and reduce the battery impedance; but if the amount is too small or the second additive is not added to the electrolyte, the battery cycle performance cannot be effectively improved and the battery impedance cannot be reduced; and if the amount is too large, the battery cell performance will not continue to be improved. Therefore, the amount of the first additive is suitable to be controlled within the range of 0.01%N1%, and the optimal amount is 0.1N0.3%.
[0085] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. An electrolyte, characterized in that: The invention comprises an electrolyte, a solvent and an additive, wherein the additive comprises at least a first additive and a second additive, and the first additive is selected from a silicon-oxygen compound containing an unsaturated bond whose chemical formula is shown in formula (I): In formula (I), R1, R2, R3, R4 and R5 are each selected from at least one of tert-butyl, 1,1-dimethoxyethyl ether and 1,1-diethylpropyl; The second additive is selected from carbodiimide compounds having a general chemical formula as shown in formula (II): R6-N=C=N-R7 (II), In formula (II), R6 and R7 are each selected from at least one of a substituted or unsubstituted alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 12 carbon atoms, or a substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms; if substituted, the substituent is a halogen or an alkyl group having 1 to 12 carbon atoms.
2. The electrolyte according to claim 1, characterized in that: Based on the total mass of the electrolyte, the mass percentage of the first additive is 0.1% to 3%.
3. The electrolyte according to claim 1, characterized in that: Based on the total mass of the electrolyte, the mass percentage of the second additive is 0.01% to 1%.
4. The electrolyte according to claim 1, characterized in that: The electrolyte is a lithium salt, and the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonylimide, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, lithium difluorooxalatoborate, lithium difluorophosphate or lithium trifluoromethylsulfonate.
5. The electrolyte according to claim 4, characterized in that: The lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the mass percentage of lithium hexafluorophosphate in the electrolyte is greater than the mass percentage of lithium bis(fluorosulfonyl)imide in the electrolyte.
6. The electrolyte according to claim 5, characterized in that: Based on the total mass of the electrolyte, the mass percentage of the lithium hexafluorophosphate is 11% to 15%, and the mass percentage of the lithium bis(fluorosulfonyl)imide is 1% to 3%.
7. The electrolyte according to claim 1, characterized in that: The solvent is selected from at least one of carbonate solvents, carboxylate solvents, ether solvents or nitrile solvents.
8. A lithium ion battery, characterized in that: The electrolyte comprises the electrolyte according to any one of claims 1 to 7.
9. The lithium-ion battery according to claim 8, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer coated on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material; The negative electrode active material is selected from at least one of silicon, silicon oxide compounds or silicon carbon compounds; or, the negative electrode active material includes a first negative electrode active component and a second negative electrode active component, the first negative electrode active component is selected from at least one of silicon, silicon oxide compounds or silicon carbon compounds, and the second negative electrode active component is selected from at least one of graphite, soft carbon, hard carbon, artificial graphite or natural graphite.
10. The lithium-ion battery according to claim 8, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer coated on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material; The positive electrode active material is selected from at least one of lithium nickel manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide.
Citation Information
Patent Citations
Electrolyte suitable for high-voltage lithium ion battery
CN103545552A
Electrolyte and battery comprising same
CN116365030A
Non-aqueous electrolyte and lithium manganese iron phosphate battery
CN116845354A
Dewatering additive, electrolyte and lithium ion battery
CN117691188A
Electrolyte and lithium ion battery
CN119324253A